Health Status of Patients With β-Thalassemia in the West Bank: A Retrospective-Cohort Study - Aldwaik, Reem; Abu Mohor, Tamara; Idyabi, Israa; Warasna, Salam; Abdeen, Shatha; Karmi, Bashar; Abu Seir, Rania (Frontiers in Medicine, 2021)
Management of β-thalassemia in developing countries is demanding in the absence of available therapies rather than recurrent transfusions. This study describes the characteristics and evaluates the hematological, biochemical, and hormonal findings of β-thalassemia patients in the West Bank. We conducted a retrospective cohort study between January 2017 and December 2018. Data were collected through β-thalassemia patients’ medical files from eight primary healthcare clinics, nine emergency departments, and eleven governmental hospitals across the West Bank. Results of the hematological, biochemical, and hormonal evaluations, in addition to demographic data and the use of iron chelation were included in the study and analyzed. A total of 309 β-thalassemia patients were included with a male-to-female ratio of 1:1 and an average age of 23.4±10.4 years. Anemic presentation was reported in 78.6% of the patients as indicated by hemoglobin level (mean±SD= 8.4±1.4 g/dL), and 73.1% had iron overload with serum ferritin (SF) levels ≥1000 µg/L (mean±SD= 317.8±3378.8 µg/L). Evaluation of liver function tests showed that alanine transaminase (ALT) and aspartate transaminase (AST) levels were high among 38.1% and 61.2% of the patients, respectively. ALT and AST showed significant positive correlations with SF levels, while kidney tests did not. As for iron chelation medications, patients receiving Deferoxamine (26.5%) showed significantly higher SF levels compared to patients receiving Deferasirox (73.5%). This study highlights the importance of establishing patient-tailored comprehensive assessment and follow-up protocols for the management of β-thalassemia with an emphasis on blood transfusion and iron chelation practices.